2011
DOI: 10.1002/cncr.26313
|View full text |Cite
|
Sign up to set email alerts
|

Final 5‐year results of Z‐FAST trial

Abstract: BACKGROUND: Postmenopausal breast cancer (BC) patients receiving adjuvant aromatase inhibitor therapy are at risk of progressive bone loss and fractures. Zoledronic acid inhibits osteoclastic bone resorption, is effective in maintaining bone health, and may therefore be beneficial in this setting. METHODS: Overall, 602 postmenopausal women with early, hormone receptor-positive BC receiving adjuvant letrozole were randomized (301 each group) to receive upfront or delayed-start zoledronic acid (4 mg intravenousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(66 citation statements)
references
References 32 publications
(44 reference statements)
1
64
0
1
Order By: Relevance
“…19 In the companion North American trial to ZO-FAST (the ZometaFemara Adjuvant Synergy Z-FAST study; n ¼ 602), immediate zoledronate also reduced disease recurrence, but did not result in a statistically significant difference in disease-free survival compared with the delayed-zoledronate group (16 vs 21 at 61 months' follow-up) ( Table 1). 20 However, taken together these findings [17][18][19][20] suggested that zoledronate may improve diseasefree survival in breast cancer patients.…”
Section: Clinical Evidence Supporting Antitumor Activity Of Bisphosphmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In the companion North American trial to ZO-FAST (the ZometaFemara Adjuvant Synergy Z-FAST study; n ¼ 602), immediate zoledronate also reduced disease recurrence, but did not result in a statistically significant difference in disease-free survival compared with the delayed-zoledronate group (16 vs 21 at 61 months' follow-up) ( Table 1). 20 However, taken together these findings [17][18][19][20] suggested that zoledronate may improve diseasefree survival in breast cancer patients.…”
Section: Clinical Evidence Supporting Antitumor Activity Of Bisphosphmentioning
confidence: 99%
“…19 Although not statistically significant, locoregional recurrences in the Z-FAST trial also occurred in slightly more patients in the delayed-zoledronate group compared with the immediatezoledronate group (4 vs 2 at 61 months' follow-up). 20 Thus, zoledronate released from bone might therefore block tumor self-seeding. Additionally, zoledronate could block mechanisms of secondary spread from bone by inhibiting the recruitment of bone marrow-derived cells to sites of premetastatic niches.…”
Section: Clinical Evidence Supporting Antitumor Activity Of Bisphosphmentioning
confidence: 99%
“…4 mg zoledronic acid twice a year) to prevent AIBL in women with a high fracture risk [33]. These results were confirmed by 4 randomized controlled studies with more than 4,000 women with BC, who were treated with an AI [48,49,50,51]. …”
Section: Therapy With Bisphosphonates and Denosumab To Prevent Aiblmentioning
confidence: 89%
“…The oral bisphosphonate risedronate has been found to be effective in preventing chemotherapyinduced bone loss in premenopausal women [33]. In the Z-FAST study, 602 postmenopausal patients receiving adjuvant letrozole therapy were randomized to upfront vs. delayed zoledronate therapy (in the delayed group therapy was started if the BMD decreased to −2.0) [36]. In the companion studies ZO-FAST and E-ZO-FAST, similar results were found, despite the fact that the 3 studies included patients from different geographical areas [37,38].…”
Section: The Prevention Of Adjuvant Breast Cancer Therapy-induced Bonmentioning
confidence: 99%